Anesthesia and the developing brain: a way forward for clinical research. Issue 5 (27th March 2015) - Davidson, Andrew J.; Becke, Karin; de Graaff, Jurgen; Giribaldi, Gaia; Habre, Walid; Hansen, Tom; Hunt, Rodney W.; Ing, Caleb; Loepke, Andreas; McCann, Mary Ellen; Ormond, Gillian D.; Pini Prato, Alessio; et al.
Summary It is now well established that many general anesthetics have a variety of effects on the developing brain in animal models. In contrast, human cohort studies show mixed evidence for any association between neurobehavioural outcome and anesthesia exposure in early childhood. In spite of large volumes of research, it remains very unclear if the animal studies have any clinical relevance; or indeed how, or if, clinical practice needs to be altered. Answering these questions is of great importance given the huge numbers of young children exposed to general anesthetics. A recent meeting in Genoa brought together researchers and clinicians to map a path forward for future clinical studies. This paper describes these discussions and conclusions. It was agreed that there is a need for large, detailed, prospective, observational studies, and for carefully designed trials. It may be impossible to design or conduct a single study to completely exclude the possibility that anesthetics can, under certain circumstances, produce long‐term neurobehavioural changes in humans; however, observational studies will improve our understanding of which children are at greatest risk, and may also suggest potential underlying etiologies, and clinical trials will provide the strongest evidence to test the effectiveness of different strategies or anesthetic regimens with respect to better neurobehavioral outcome.